Writing as skin: Negotiating the body in(to) learning about the managed self. Issue 1 (February 2019) - Brewis, Deborah N; Williams, Eley
We draw on the notion of 'skin' to discuss the ways in which writing in management and organisation studies wrestles with two drives in its endeavour to represent the reality of our 'organised' lives: the drive to share internal lived experience, and the drive to externalise and abstract. Through exploring skin as a metaphor for a negotiating interface between these forces in our writing, we (a) argue that both are critical parts of writing, needed in order to learn about management and organisation and (b) explore different ways in which they might be brought into contact. Reviewing, synthesising and building on critiques of 'scientific' writing that have been made from within management and organisation studies, and on creative commentary from the arts, we think reflexively about the ways in which writing mediates learning by being both representative of experience and an experience in itself. A collaboration between management scholar and creative writer, the text of this article is a critical-creative experiment that outlines the experiential 'skin-text' while simultaneously producing an example of such a text.